The impact of performance appraisal program on selected employees of government agencies in Iloilo City - Amen, Ligaya; Galleto, Arlen; Maglente, Grace; Nismal, Hazel; Velez, Roderick
This study evaluated the impact of performance appraisal on employees of selected government agencies in Iloilo City. Eight agencies participated in this research, DTI, PIA, NSO, GSIS, DENR, DECS, DILG, and DA. The researchers aimed (1) to know if government agencies in Iloilo City conduct performance appraisal; (2) to know what are the factors that they consider in assessing their employees, and whether the results are being communicated to the employees; (3)to know if the attitude of the employees toward performance appraisal varies with sex, age, and civil status; (4) to know if there exist a positive correlation between attitude toward performance appraisal and attitude toward work; (5) to determine the factors that affect the effectiveness of the appraisal program. Pre-survey was conducted to get the necessary information needed prior to the actual data gathering. The rest of the date were collected through the use of questionnaires. Results revealed that employees regarded performance appraisal positively. However, it failed to have a significant correlation with the attitude toward work. Generally, appraisal program was considered essential in attaining goals that are beneficial to both management and the employees.